2003
DOI: 10.1097/00002030-200312050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HLA-B57 on clinical presentation and viral control during acute HIV-1 infection

Abstract: These data demonstrate that host genetic factors can influence the clinical manifestations of acute HIV-1 infection and provide a functional link between HLA-B57 and viral immune control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
259
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(281 citation statements)
references
References 52 publications
17
259
2
3
Order By: Relevance
“…HLA-B*57 is an HLA allele previously reported to be associated with slow HIV disease progression (9,(38)(39)(40). It has been reported that CD8 + T cell responses restricted by this allele may have unique qualities that influence the efficiency with which they control HIV (41)(42)(43). For example, CD8 + T cell responses restricted by HLA-B*57 contribute more to the total HIV-specific response during early infection, recognize a greater fraction of potential HIV-restricted epitopes, and are associated with a reduction in the level of the response restricted by other alleles carried by the same individual (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…HLA-B*57 is an HLA allele previously reported to be associated with slow HIV disease progression (9,(38)(39)(40). It has been reported that CD8 + T cell responses restricted by this allele may have unique qualities that influence the efficiency with which they control HIV (41)(42)(43). For example, CD8 + T cell responses restricted by HLA-B*57 contribute more to the total HIV-specific response during early infection, recognize a greater fraction of potential HIV-restricted epitopes, and are associated with a reduction in the level of the response restricted by other alleles carried by the same individual (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, neutralizing antibody responses exert ''soft'' selection pressure (67), by affecting the relative fitness of different strains present in the viral quasispecies. In contrast, cellular immune responses may exert ''hard'' selection pressure (67), in which the absolute fitness of the population is affected, suggested by the correlation of CTL responses and class I HLA alleles with viral load (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…The HLA-B*57:01 allele is associated with slower HIV-1 disease progression 15,16,17,18,19 and autoimmune reactions, including hypersensitivity, to the anti-viral drug abacavir 20,21,22 . In HIV-1-infected individuals, the expressed HLA-B*57:01 allomorph elicits robust CD8 + T-cell responses that are thought to control viremia.…”
Section: Introductionmentioning
confidence: 99%